First measurement of hadronic event shapes in pp collisions at root s=7 TeV - Khachatryan, V; Sirunyan, A; Tumasyan, A; Adam, W; Bergauer, T; Dragicevic, M; Eroe, J; Fabjan, C; Friedl, M; Fruehwirth, R; Ghete, V; Hammer, J; et al. (2011)
Hadronic event shapes have been measured in proton-proton collisions at s=7 TeV, with a data sample collected with the CMS detector at the LHC. The sample corresponds to an integrated luminosity of 3.2 pb-1. Event-shape distributions, corrected for detector response, are compared with five models of QCD multijet production. © 2011 CERN.